Editorial: Modern Fractional Dynamic Systems and Applications, Mfdsa 2017 Special Issue in Honor of: R.P. Agarwal, D. Baleanu, J.J. Nieto, D.F.M. Torres and y. Zhou. Highly Cited Researchers in the Field. - Lizama-Yanez, C (Elsevier B.V., 2018)
[No abstract available]